The impact of COVID-19 on the everyday life of blind and sighted individuals - Gori, Monica; Bertonati, Giorgia; Mazzoni, Emanuela; Freddi, Elisa; Amadeo, Maria Bianca (Frontiers in Psychology, 2022)
The COVID-19 pandemic caused unexpected and unavoidable changes in daily life worldwide. Governments and communities found ways to mitigate the impact of these changes, but many solutions were inaccessible to people with visual impairments. This work aimed to investigate how blind individuals subjectively experienced the restrictions and isolation caused by the COVID-19 pandemic. To this end, a group of twenty-seven blind and seventeen sighted people took part in a survey addressing how COVID-19 impacted life practically and psychologically, how it affected their daily habits, and how it changed their experiences of themselves and others. Results demonstrated that both sighted and blind individuals had a hard time adapting to the new situation. However, while sighted people struggled more with personal and social aspects, the frustration of the blind population derived mostly from more practical and logistical issues. Likely as consequences, results showed that blind people engaged more in their inner life and experienced fear and anger as main emotions. This study suggests that changes in life associated with COVID-19 have been subjectively experienced differently based on the presence or not of blindness, and that tailored future interventions should be considered to take care of the different needs of blind individuals.